Application Of The AHP Method In A Decision Support System For Used Car Selection Recommendations - Istiqomah Istiqomah; Firrahmi Rizky; Etty Harya Ningsi (INFOKUM, 2025)
The selection of used cars often becomes a complicated matter for consumers who lack knowledge about cars. According to the owner of the Mobilku Sumut Aceh showroom, many aspects need to be considered, such as engine condition, year of manufacture, price, and physical condition. This study aims to design a decision support system (DSS) using the Analytic Hierarchy Process (AHP) method to provide recommendations for selecting used cars. The AHP method was chosen for its ability to break down complex problems into a hierarchical structure and compare criteria pairwise to determine priority weights. This analysis allows consumers to adjust their preferences for specific criteria, such as budget or specific features. Based on testing results, this analysis is capable of providing recommendations that match the needs and preferences of consumers, thereby helping them make more targeted and effective decisions. This study is expected to simplify the decision-making process for purchasing used cars for consumers at the Mobilku Sumut Aceh showroom.